Synthetic media for preservation of corneal tissues deemed for endothelial keratoplasty and endothelial cell culture. Issue 3 (10th September 2020) - Parekh, Mohit; Ruzza, Alessandro; Gallon, Paola; Ponzin, Diego; Ahmad, Sajjad; Ferrari, Stefano
Abstract: Purpose: To compare the difference between various endothelial graft preparation methods and endothelial cell culture from tissues that are preserved in serum‐based and synthetic medium. Methods: In a randomized masked study, the tissues ( n = 64) were preserved in Cornea Max (serum‐based) and Cornea Syn (synthetic) series for 36 days at their respective preservation conditions. Following organ culture, corneal tissues ( n = 48) were used to prepareDescemet stripping automated endothelial keratoplasty (DSAEK), preloaded ultra‐thin (UT) ‐DSAEK, prestripped Descemet membrane endothelial keratoplasty (DMEK), free‐floating DMEK, and preloaded DMEK with endothelium inward and outward grafts. These tissues were preserved for another 4days at room temperature in dextran supplemented media following which they were subjected to trypan blue, alizarin red, live/dead and Zonula Occludens‐1 (ZO‐1) staining. A separate set of tissues ( n = 16) from both the series was used for human corneal endothelial cell (HCEnC) culture. At confluence, the proliferation and cell doubling rate was calculated and the cultured cells were subjected to live/dead, ZO‐1, 2A12 and Ki‐67 staining. Mann–Whitney test was performed with p < 0.05 deemed statistically significant. Results: After preparation and preservation of the tissues for endothelial keratoplasty, alizarin red showed standard endothelial morphology from both the groups. Endothelial cell loss, hexagonality and uncovered areas did not show statistically significant differences (p > 0.05) between both groups. For HCEnC, cell doubling rate was 4.7 days (p > 0.05). All the antibodies were expressed in both the groups. Hexagonality, polymorphism, cell area, viable/dead cells and Ki‐67 positivity were not statistically significant (p > 0.05). Conclusions: Complete synthetic organ culture series is safe and advantageous for carrying out advanced endothelial keratoplasty graft preparation procedures and for HCEnC culture as it is free from animal or animal‐derived products.